Faculty recognition ceremony bestowed the title of University Fellow on five eminent faculty - De La Salle University, Manila (Animo Repository, 1988)
Faculty Recognition Ceremony this year bestowed the title of University Fellow on five eminent faculty, one from each college. A University Fellow was defined in the 1987 Faculty Manual. The 1988 awardees effective January '88, were: Tereso Tullao, Jr., Servillano Olano, Jr., Emma Teodoro, Emerita Quito and Wyona Patalinghug.